Simple hysterectomy in the presence of invasive cervical cancer in Iran. Issue 2 (1st February 2003) - Behtash, N.; Mousavi, A.; Mohit, M.; Modares, M.; Khanafshar, N.; Hanjani, P.
Abstract : The objective of this study was to determine the reasons leading to an inappropriate simple hysterectomy in the presence of invasive cervical cancer. During 1997–2001, 62 cases of invasive cervical carcinoma that had been treated by simple hysterectomy were referred to the gynecology oncology service in Vali-e-Asr hospital, Tehran, Iran. Five had microinvasive carcinoma. The remaining 57 women had either adenocarcinomas or squamous cell carcinoma (SCC). Medical records were reviewed retrospectively to determine the reasons for inappropriate hysterectomy. Reasons for inappropriate hysterectomy were as follow: lack of preoperative Pap smear (P/S) (29%), deliberate hysterectomy for biopsy-proven cancer (25.8%), negative P/S (6.5%), inadequate evaluation of abnormal P/S (6.5%), failure to perform an indicated conization (3.2%), and emergent operation because of uterine perforation (1.6%). Reasons for inappropriate hysterectomy in the remainder of patients (27.4%) were not found because of lack of sufficient information. Although 45.2% of these patients had complained for vaginal bleeding, only four of them had preoperative endocervical and endometrial sampling. Despite the increasing emphasis on performing cervical cancer screening before hysterectomy, only 18 (29%) referral patients had preoperative P/S. We conclude that by close adherence to the cervical cancer screening guidelines and appropriate evaluation of the presenting symptoms, we may avoid inappropriate management of cervical carcinomas with simple hysterectomy. Many cases of simple hysterectomy in the presence of biopsy-proven squamous cell carcinoma of the cervix necessitates some reconsideration of gynecology oncology postgraduate courses for general gynecologists.